Psychoeducational intervention on knowledge and perceptions of families of schizophrenic patients under “pasung” - Siregar, Umi Fadilah; Liza, Rini Gusya; Ashal, Taufik; Semiarty, Rima; Abdiana; Handayani, Tuti (BKM Public Health and Community Medicine, 2024)
Purpose: The number of pasung cases in West Sumatra in 2020 was still relatively high, totaling 122 people. Of the 19 city districts, Padang Pariaman district is the first with the highest prevalence of pasung mental cases, 24 people. In addition to psychopharmaceutical therapy, the management of schizophrenia requires psychosocial interventions such as family psychoeducation. Families have an important role in helping schizophrenia patients to realize the pasung-free program launched by the government. Methods: Pre-experimental study by one-group pre-test and post-test design conducted in September 2021-June 2022 involving 18 families of schizophrenia patients who were shackled in the Padang Pariaman Public Health Center area. Univariate data analysis is presented as a frequency distribution and bivariate analysis using paired sample t-test and Wilcoxon test. Results: The level of knowledge before the family psychoeducation intervention was poor (94.4%), and the level of knowledge after the family psychoeducation intervention was good (55.6%), the perception before the family psychoeducation intervention was poor (88, 9%) and the perception after family psychoeducation intervention is good (50.0%), there is an effect of psychoeducation intervention on the level of knowledge of families of schizophrenia patients who are shackled p=0.001 (<0.05), and there is an effect of psychoeducation intervention on the perception of families of schizophrenia patients who are shackled p=0.001 (<0.05). Conclusion: Family psychoeducation interventions are very helpful in increasing family knowledge and perceptions of schizophrenia disorders, and it is hoped that Puskesmas Agencies will be more proactive in providing family psychoeducation to reduce the number of cases of pasung in the puskesmas working area.